2012
DOI: 10.1088/0957-4484/23/6/065701
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic electromagnetically induced transparency in metallic nanoparticle–quantum dot hybrid systems

Abstract: We study the variation of the energy absorption rate in a hybrid semiconductor quantum dot-metallic nanoparticle system doped in a photonic crystal. The quantum dot is taken as a three-level V-configuration system and is driven by two applied fields (probe and control). We consider that one of the excitonic resonance frequencies is near to the plasmonic resonance frequency of the metallic nanoparticle, and is driven by the probe field. The other excitonic resonance frequency is far from both the plasmonic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 29 publications
0
49
0
3
Order By: Relevance
“…Internal photoemission which is usually described by an escape cone model is more efficient at lower wavelengths, with the free-carrier absorption expected to be proportional to λ 2 causing the responsivity to increase as wavelength increases. At long wavelengths, the free-carrier absorption is independent of the wavelength and the responsivity decreases with increasing wavelength due to the decreasing internal photoemission [6,12,13,17]. The characteristics of the photoconductive CdS quantum devices suggest that they are good candidates for optoelectronic M a n u s c r i p t switches, with the dark insulatingstate as "OFF" and the light-exposed conducting state as "ON".…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Internal photoemission which is usually described by an escape cone model is more efficient at lower wavelengths, with the free-carrier absorption expected to be proportional to λ 2 causing the responsivity to increase as wavelength increases. At long wavelengths, the free-carrier absorption is independent of the wavelength and the responsivity decreases with increasing wavelength due to the decreasing internal photoemission [6,12,13,17]. The characteristics of the photoconductive CdS quantum devices suggest that they are good candidates for optoelectronic M a n u s c r i p t switches, with the dark insulatingstate as "OFF" and the light-exposed conducting state as "ON".…”
Section: Resultsmentioning
confidence: 99%
“…In 2000 S. Datta et al demonstrated the schottky junction of Ag with CdTe, CdS, ZnO; its characteristics and PV device application [1][2][3][4][5]. M. R. Singh et al demonstrated the optical switching nano-devices of metallic nanoparticle -quantum dot hybrid system ,where the photonic crystal allows to switch the absorption of the metal particle at a given frequency range when the excitonic frequencies lie near the band edge [6]. We have fabricated Ag NCs/CdS (CdS: Cu) quantum dots schottky junction and characterized for electrical and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The first term in Eq. (3) indicates in the limit in which the calculated electric field distribution is dominated by dipole modes, this factor is directly related to the photoluminescence radiative decay rate enhancement of the QD [11,18,38,45]. As a result, Γ r P enh ðω e Þ represents the enhanced radiative decay rate of excitons in je〉.…”
Section: Spontaneous Emission Of Qds Under Incoherent Pumping Regimementioning
confidence: 99%
“…This term contains energy relaxation processes associated with diagonal elements of the density matrix and dephasing of the off-diagonal elements. Except for the contribution of FRET, this term is treated in this paper in a phenomenological way [38]. …”
Section: Spontaneous Emission Of Qds In the Presence Of Coherent Excimentioning
confidence: 99%
See 1 more Smart Citation